Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi dalam Pengambilan Sertifikasi Akuntansi - Dianah Herlina Putri; Viola Syukrina E Janrosl (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the factors influencing accounting students' interest in obtaining accounting certification. This type of research is quantitative. The data used in this study are primary data. The data collection technique used is a questionnaire method in the form of statements distributed using Google Forms with a 5-point Likert scale measurement. The population of this study includes accounting students in the odd semester of 2023 at Universitas Internasional Batam, Universitas Universal, and Universitas Riau Kepulauan, totaling 981 students. The sample was selected using purposive sampling with the Slovin formula, resulting in a sample size of 91 respondents. The software used for data testing in this study is SPSS version 25. The tests in this study include validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, partial tests (t-tests), simultaneous tests (F-tests), and determination coefficient tests (R²). The results of this study indicate that career motivation partially influences accounting students' interest in obtaining accounting certification (Chartered Accountant), the level of understanding does not partially influence accounting students' interest in obtaining accounting certification (Chartered Accountant), and cost perception partially influences accounting students' interest in obtaining accounting certification (Chartered Accountant). Additionally, career motivation, level of understanding, and cost perception simultaneously influence accounting students' interest in obtaining accounting certification (Chartered Accountant).